Development of Media Interactive Problem Based Learning Android-Assisted to Improve Student at SMA Negeri 10 Medan - Alexander Sitinjak (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to develop learning media using that are valid, practical, and effective to improve students' ability to understand flat Derivative topics. The study was carried out at SMA NEGERI 10 MEDAN. The subjects of this research were students of class XI IPA-1. This research is research and development (R&D) using the ADDIE Model. The data collection technique uses a questionnaire assessment sheet for material experts, teaching material experts, learning practitioners and student responses. The results showed that learning media using Android Studio obtained an average percentage of 91.8% with the criteria of